DESKRIPSI TINGKAT FERTILITAS TOTAL ( TOTAL FERTILITY RATE ) PROVINSI GORONTALO - Tisen Tisen (LPPM Universitas Muhammadiyah Gorontalo, 2019)
The increase in TFR is predicted to have a negative impact on the Government and the community. The ASFR factor is one of the demographic factors that is closely related to TFR, the studied is to get a picture and control solution, especially in the Goron talo province. The data used in this paper is the data of Gorontalo Province’s SKAP 2018 in 2018, the population of this survey is WUS (15 to 49 years), families and adolescents aged 15 to 24 years are not married and house holds in sele cted clusters . The sampling design used stratified multistage sampling , with a total of 48 clusters selected . Each cluster was enumerated and 35 Eligible House hold were selected using the systematic random sampling technique to be interviewed. Survey results show Gorontalo Province TFR is 2.46 children per woman, increased by 2.43 percent compared to the results of the 2017 RPJMN Survey, higher than the National average TFR which reached 2.38. The highest TFR is closely related to the ASFR of 15 - 19 Years old group of 52 (52 births per 1000 women). The shift age with the highest fertility rates from 20 - 24 years to 25 - 29 years old, each shift age reached 142 and 150 births per 1000 women in each group. The high ASFR in the young age group has the potential to increase TFR. Peningkatan TFR diprediksi mampu memberi dampak buruk bagi Pemerintah dan masyarakat sendiri. Faktor ASFR merupakan salah satu faktor demografi yang berkaitan erat dengan TFR sehingga diperlukan suatu kajian untuk mendapatkan gambaran dan solusi pengendalian khususnya di wilayah provinsi Gorontalo. Data yang digunakan dalam makalah ini merupakan data SKAP 2018 Provinsi Gorontalo Tahun 2018, populasi dari survei ini adalah WUS (15 Sampai 49 Tahun), keluarga dan remaja usia 15 sampai 24 Tahun belum menikah dan rumah tangga pada klaster terpilih. Rancangan sampling yang digunakan adalah stratified multistage sampling, dengan jumlah klaster terpilih sebanyak 48 klaster. Masing-masing klaster dilakukan pencacahan dan dipilih 35 Rumah Tangga Eligible dengan menggunakan teknik sistematic random sampling untuk diwawancarai. Hasil Survei menunjukkan TFR Provinsi Gorontalo adalah 2,46 anak per wanita, meningkat 2,43 persen dibanding dengan hasil Survei RPJMN 2017 lebih tinggi dibandingkan TFR rata-rata Nasional yang mencapai 2,38. Tingginya TFR ini berkaitan erat dengan ASFR kelompok umur 15-19 Tahun sebesar 52 (52 kelahiran setiap 1000 wanita). pergeseran usia dengan tingkat fertilitas tertinggi dari usia 20-24 Tahun menjadi usia 25-29 tahun, yang masingmasing mencapai 142 dan 150 kelahiran per 1000 wanita pada masing-masing kelompok. Tingginya ASFR pada kelompok usia muda berpotensi meningkatkan TFR.